Idiom Analysis in Covid-19 News at the Thejakartapost.com Online Newspaper Period 1st-5th February 2021 - Mahuda Safitri; Retno Fitriani; Septi Titin Nurochman; Rahmania Firdaus (JOSAR (Journal of Students Academic Research), 2016)
Idiom is a word the meaning of which cannot be defined by a literal description.The types of idiom are: 1) Phrasal verb, 2) Prepositional phrases, 3) Idioms with verbs as keywords, 4) Idioms with nouns as keywords, 5) Idioms with adjectives as keywords: cold comfort, wishful thinking, plan sailing, 6) Idiomatic pairs, 7) Grammatica Restriction, 8) Phrasal verb, 9)other language, 10)binomial. The purpose of this research is to determine the idioms used in news items. This research uses a qualitative type of research with methods that are literature studies. The steps in the research are as follows: read to the news in an online newspaper, recording the idioms found with note them, describing the meaning of these idioms and making conclusions from the research results.